CONCRETE SHEAR STRENGTH TEST USING BEACH SAND AS FINE AGGREGATE AND SIKACIM CONCRETE ADDITIVE AS ADDED MATERIAL - Zulkarnain, Fahrizal; Putri Aulia; Sri Frapanti (Jurnal Teknik Sipil : Rancang Bangun, 2024)
Concrete has become one of the most important building materials for the real estate and civil construction industry. This study aims to create new innovations in the world of constructions namely by utilizing materials available in nature namely beach sand as fine aggregate with the addition of Sikacim Concrete Additive to concrete mix. In addition, this study is intended to determine what if beach sand is used as fine aggregate and Sikacim Concrete Additive as an additive to the shear strength value of concrete. With variations of BTN, BTPP (30%, 50%, 70%), and BTPP (30%, 50%, 70%) + Sikacim Concrete Additive (0,8%) by weight of cement. The samples used were beams with dimensions of (60 cm x 15 cm x 15 cm) with a total of 21 specimens. Shear strength testing can be done if the concrete is 28 days old. The shear strength value obtained of BTN is 1,08 MPa, BTPP 30% is 0,91 MPa, BTPP 50% is 0,78 MPa, BTPP 70% is 0,73 MPa, BTPPS 30% is 1,21 MPa, BTPPS 50% is 1,04 MPa, dan BTPPS 70% is 0,96 MPa. The optimum shear strength value was obtained at the BTPPS 30%.